Primary events in the photodissociation of oxyhemoglobin. Issue 3 (2010) - Yabushita, Atsushi; Kobayashi, Takayoshi
Abstract : The growing number of data on heme proteins in the ultrafast time domain have revealed complicated photophysics of the heme that are sensitive both to the structure of the protein and to the ligand species. In this work, ultrafast time-resolved pump–probe in visible spectral range was performed using an ultrashort visible laser pulse. Broad spectral width of visible laser pulse enabled us to observe the pump–probe signal with a broadband range. A broadband multi-channel detector array coupled to a multi-channel lock-in amplifier was used to obtain the pump–probe signals at all of the probe frequencies simultaneously. In the simultaneous measurement at many probe wavelengths, we could obtain ultrafast spectral change after the photo-excitation of oxy-hemoglobin only with a short measurement time, avoiding laser damage on the sample. The time constant of the primary process was determined for the first time. Ultrafast spectral change observed in the early delay time region directly shows ultrafast photo-dissociation process of oxy-hemoglobin.